2021
DOI: 10.3389/fonc.2021.665832
|View full text |Cite
|
Sign up to set email alerts
|

Chlorpromazine Sensitizes Progestin-Resistant Endometrial Cancer Cells to MPA by Upregulating PRB

Abstract: Medroxyprogesterone acetate (MPA) is the main conservative treatment for endometrial cancer (EC) patients desirable to preserve fertility and those who cannot suffer from surgery. Considering the high incidence of progestin resistance and recurrence of MPA treatment, we reproposed antipsychotics chlorpromazine (CPZ) as a new strategy for both progestin-sensitive and -resistant endometrial cancer. Cytobiology experiments indicated that CPZ could significantly suppress proliferation, migration/invasion and induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…[ 40 ] CPZ, which belongs to the phenothiazine class of antipsychotic drugs, was identified as a potential candidate for drug repurposing in cancer treatment, specifically for EC. [ 7 , 36 ] It has been reported to have anti‐proliferative effects, as it alters the expression of proteins that regulate the cell cycle and intracellular mitochondrial functions. [ 41 , 42 , 43 , 44 ] However, the repurposing of CPZ for cancer therapy is challenging, as CPZ is a first‐generation antipsychotic that also has some serious limitations, such as extrapyramidal symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 40 ] CPZ, which belongs to the phenothiazine class of antipsychotic drugs, was identified as a potential candidate for drug repurposing in cancer treatment, specifically for EC. [ 7 , 36 ] It has been reported to have anti‐proliferative effects, as it alters the expression of proteins that regulate the cell cycle and intracellular mitochondrial functions. [ 41 , 42 , 43 , 44 ] However, the repurposing of CPZ for cancer therapy is challenging, as CPZ is a first‐generation antipsychotic that also has some serious limitations, such as extrapyramidal symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] In particular, the utilization of antipsychotics for EC has been an area of ongoing research, but the targets of these investigations remain unclear. [ 7 ] Preliminary screening of 20 tricyclic antipsychotic drugs for an anti‐EC phenotype against 1400 approved drugs in our library revealed that the phenothiazine medicine chlorpromazine (CPZ), which has been widely used as an antipsychotic drug, also has strong anti‐EC activity. Through traditional drug structure optimization, the CPZ derivatives JX57 and JX66 were developed and found to have stronger anti‐EC activities than CPZ in vitro and in vivo ( Figure 1 A ), with minor extrapyramidal side effects.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that Nrf2 plays an important role in the development of progestin resistance while Nrf2 could lead to the progression of cell cycle by activating Akt pathway [ 41 ]. It was also reported that chlorpromazine reverses progestin resistance by inhibiting PI3K-Akt pathway [ 42 ]. So PI3K-Akt pathway may be a key link in regulating progestin resistance of EC.…”
Section: Discussionmentioning
confidence: 99%
“…Antipsychotic agents, including chlorpromazine (CPZ) and thioridazine (THIO), exert anti-oncogenic and progestin-sensitizing effects in EC. It was found that low-dose CPZ (5 mM) pre-treatment could effectively upregulate PRB expression [ 186 ]. Additionally, CPZ downregulated IGF-1R expression and induced PI3K/AKT phosphorylation, thereby inhibiting the development of EC [ 186 ].…”
Section: Potential Therapeutic Methods To Enhance Progestin Sensitivitymentioning
confidence: 99%
“…It was found that low-dose CPZ (5 mM) pre-treatment could effectively upregulate PRB expression [ 186 ]. Additionally, CPZ downregulated IGF-1R expression and induced PI3K/AKT phosphorylation, thereby inhibiting the development of EC [ 186 ]. Another antipsychotic drug, THIO, combined with MPA, may suppress the development of EC and enhance progestin sensitivity by upregulating the PRB expression and downregulating the EGFR expression.…”
Section: Potential Therapeutic Methods To Enhance Progestin Sensitivitymentioning
confidence: 99%